Rapid Maxillary Expansion: Updated Review of Available Techniques - Soto, Felipe (2024)
The transverse deficiency of the maxilla is a dentomaxillary anomaly capable of producing functional problems in occlusion, respiration and esthetics. Its traditional clinical presentation is dental crowding, which obstructs the correct eruption of the teeth. Its management corresponds to rapid maxillary expansion, which can be assisted by means of mini-implants (MARPE), surgery (SARPE) or a combination of both techniques (MISMARPE). The objective of this article is to present a contrast between the techniques used in rapid maxillary expansion to simplify clinical decision making. A narrative review was performed in PubMed, Scopus and Epistemonikos databases, including systematic reviews, meta-analyses, randomized clinical trials and observational studies published between 2013 and 2023. A total of 23 articles were included, which met the established inclusion and exclusion criteria. The clinical management of transverse deficiency of the maxilla frequently requires an interdisciplinary management, combining an orthopedic and surgical approach. As found in the current review, all techniques; MARPE, SARPE and MISMARPE, report indications and limitations, as well as associated complications. It is recommended to deepen and prolong the study of new techniques in order to analyze their long-term stability in comparison to other therapeutic currents.